The Multifaceted Roles of MYC2 in Plants: Toward Transcriptional Reprogramming and Stress Tolerance by Jasmonate Signaling - Song, Cheng; Cao, Yunpeng; Dai, Jun; Li, Guohui; Manzoor, Muhammad Aamir; Chen, Cunwu; Deng, Hui (Frontiers in Plant Science, 2022)
Environmental stress is one of the major restrictions on plant development and foodstuff production. The adaptive response in plants largely occurs through an intricate signaling system, which is crucial for regulating the stress-responsive genes. Myelocytomatosis (MYC) transcription factors are the fundamental regulators of the jasmonate (JA) signaling branch that participates in plant development and multiple stresses. By binding to the cis-acting elements of a large number of stress-responsive genes, JA-responsive transcription factors activate the stress-resistant defense genes. The mechanism of stress responses concerns myriad regulatory processes at the physiological and molecular levels. Discovering stress-related regulatory factors is of great value in disclosing the response mechanisms of plants to biotic or abiotic stress, which could guide the genetic improvement of plant resistance. This review summarizes recent researches in various aspects of MYC2-mediated JA signaling and emphasizes MYC2 involvement in plant growth and stress response.